Impact of glomerular filtration estimate on bleeding risk in very old patients treated with vitamin K antagonists - Poli, Daniela; Antonucci, Emilia; Zanazzi, Maria; Grifoni, Elisa; Testa, Sophie; Ageno, Walter; Palareti, Gualtiero (Thrombosis and Haemostasis, 2012)
Vitamin K antagonists (VKA) therapy is increasingly used in elderly for prevention of venous thromboembolism (VTE) and of stroke in atrial fibrillation (AF). Glomerular filtration rate (GFR), usually estimated from different equations, decreases progressively with age and it is a risk factor for bleeding. In the frame of the EPICA study, a multicentre prospective observational study including 4,093 patients ≥80 years naïve to VKA treated for AF or after VTE, we performed this ancillary study to evaluate the prevalence of chronic kidney diseases (CKD) by estimated GFR (eGFR). Incidence of bleedings was recorded and bleeding risk was evaluated in relation to eGFR calculated by Cockroft-Gault (C-G); Modification of Diet in Renal Disease (MDRD) and Chronic Kidney Disease Epidemiology Collaboration (CKD-EPI) formulas. In addition, the agreement among the three eGFR formulas was evaluated. We recorded 179 major bleedings (rate 1.87 x100 patient-years [py]), 26 fatal (rate 0.27 x100 py). Moderate CKD was detected in 69.3%, 59.3% and 47.0% and severe CKD in 5.8%, 7.4% and 10.0% of cases by C-G, MDRD and CKD-EPI, respectively. Bleeding risk was higher in patients with severe CKD irrespective of the applied equation. This study confirms that CKD represents an independent risk factor for bleeding and that a wide proportion of elderly on VKA had severe or moderate CKD, suggesting the need for frequent monitoring. Although the different available equations yield different eGFR, all appear to similarly predict the risk of major bleeding.
Keywords: Bleeding; elderly; glomerular filtration rate; VKA treatment